Socio-Cultural study of new autonomous region (NAR) Central Papua Province Indonesia - Siregar, Leonard; Lekitoo, Hanro Y. (International Journal on Social Science, Economics and Art, 2024)
The development of a region in a country is a strategic policy aimed at improving the welfare of the people living in the area. Development efforts made by the government often encounter obstacles that result in efforts to develop welfare not being maximized. The purpose of this study is to try to identify social and cultural problems that occur in the new autonomous region as a result of regional expansion in Central Papua Province. The method used in data collection is a mix method that combines quantitative methods with qualitative methods. The purpose of using this method is to obtain more comprehensive, valid, reliable and objective data. In this study, qualitative data is used to explain quantitative data. The socio-cultural economic conditions of Central Papua Province as a new autonomous region (DOB) face many challenges in implementing development. The problems faced are related to health, education and security. In terms of security, it is often triggered by social jealousy between community groups which leads to criminal acts.